Temporal variation and heterogeneity of avifauna in the Bangladesh national museum premises - Khan, Shawkat Imam (Journal of the Asiatic Society of Bangladesh, Science, 2026)
The study on temporal variation and heterogeneity of avifauna was carried out in the Bangladesh national museum premises during May 2018 to April 2019 employing Strip Transect Sampling technique. A total of 46 species of birds belonging to 11 orders, 26 families and 40 genera were recorded. Of which, 21 species were passerines and 25 non-passerines, 40 were resident and 6 migratory. Family Ardeidae and Sturnidae constituted the highest number of species (n=4, 8.7%of total). Only a single species were recorded from each of the 13 families. The maximum numbers (33%) of species were locally rare. Insectivorous birds were the highest (n=18,39.13% of total) than the other type of birds (piscivorous, frugivorous, omnivorous, granivorous, scavengers, nectarivorous and carnivorous). The highest number of species were (36.22%) recorded during winter than the other two seasons and the species heterogeneity was negatively correlated with temperature (y = -0.011x + 1.118, R2 = 0.262) and precipitation (y = -0.000x + 0.835, R2 = 0.048) of the study area. The Euclidean distance between the recorded birds in monsoon and winter are much closer than summer. One third of the recorded birds (31.11% of total) used the tree holes, bank of the pond, tree canopies and roof top of the main building of the Bangladesh National Museum for breeding purposes. Altogether 63 tree species (n=556 individuals) of 34 families were recorded in the premises, all of which were used by birds for different purposes. Of the total species of trees, 60% of trees were used for roosting, 30% for feeding and 11% for nesting by birds. J. Asiat. Soc. Bangladesh, Sci. 51(2): 177-192, December 2025